2021
DOI: 10.5195/jmla.2021.1185
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of gender detection tools: a comparative study of name-to-gender inference services

Abstract: Objective: To evaluate the performance of gender detection tools that allow the uploading of files (e.g., Excel or CSV files) containing first names, are usable by researchers without advanced computer skills, and are at least partially free of charge.Methods: The study was conducted using four physician datasets (total number of physicians: 6,131; 50.3% female) from Switzerland, a multilingual country. Four gender detection tools met the inclusion criteria: three partially free (Gender API, NamSor, and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 19 publications
4
79
0
Order By: Relevance
“…We recommend using genderize.io only with files that were modified in this way, as the proportion of nonclassifications was very high in file #1 (naCoded 16.4%). By comparing the results obtained with this double manipulation of first names with those already published in our earlier study [ 9 ], we observe that genderize.io is almost as efficient as Gender API (errorCoded 1.8%) and NamSor (errorCoded 2.0%), the two gender detection tools that were shown to be the most powerful.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…We recommend using genderize.io only with files that were modified in this way, as the proportion of nonclassifications was very high in file #1 (naCoded 16.4%). By comparing the results obtained with this double manipulation of first names with those already published in our earlier study [ 9 ], we observe that genderize.io is almost as efficient as Gender API (errorCoded 1.8%) and NamSor (errorCoded 2.0%), the two gender detection tools that were shown to be the most powerful.…”
Section: Discussionmentioning
confidence: 60%
“…However, this is a multicultural and multilingual country, and nationalize.io showed multiple origins of the first names, even though almost half (i.e. 47%) were of French- or English-speaking origin [ 9 ]. Although the results of this study may be generalizable to most Western names, with other names, for example Asian or Middle Eastern, the effectiveness of the method used in the study is yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations